The Islamic Perspective on Political Asylum: Analysis of The Rohingya Refugee Issue in Aceh, Indonesia - Ma'adul Yaqien Makkarateng; Lukman Arake (UIN Raden Mas Said Surakarta, 2024)
This article discusses the issue of Rohingya refugees in Aceh, Indonesia, from an Islamic perspective. The Rohingya refugees flee from violence and discrimination in Myanmar, seeking asylum in neighboring countries, including Indonesia. This research employs a qualitative method to gather and analyze data to understand the concepts, opinions, and experiences related to this issue. The findings indicate that Islam emphasizes the importance of humanity, even towards non-Muslims. The majority of Acehnese people oppose the Rohingya refugees due to concerns over economic security and social cohesion. However, they do not justify the violation of human dignity and rights. Islam teaches tolerance, justice, and kindness to all of God's creatures. Despite the challenges in handling refugees, support and cooperation from the government and the international community are crucial in seeking comprehensive long-term solutions to the Rohingya crisis. This article also examines political asylum policies from the perspective of Islamic law, emphasizing that Islam is a religion that acknowledges and respects human rights, encouraging its followers to be just and kind to all people, including non-Muslims.